Resveratrol Sensitizes Colorectal Cancer Cells to Cetuximab by Connexin 43 Upregulation-Induced Akt Inhibition - Wang, Yijia; Wang, Wenhong; Wu, Xiaojing; Li, Chunjun; Huang, Yaping; Zhou, Huiyan; Cui, Yu (Frontiers in Oncology, 2020)
Cetuximab is a monoclonal antibody that acts as an anti-epidermal growth factor receptor (EGFR) agent. Cetuximab inhibits the phosphorylation and activation of EGFR and blocks downstream signal pathways of EGF/EGFR, including Ras-Raf-MAPK and PI3K-Akt pathways. Akt activation is an important factor in cetuximab resistance. It has been reported that resveratrol and connexin 43 regulate Akt in different ways based on tissue type. Since connexin 43 interacts with Akt, and resveratrol is known to upregulate connexin 43, we investigated whether resveratrol can sensitize colorectal cancer cells to cetuximab via connexin 43 upregulation. Our work confirmed that resveratrol increases the inhibition of growth by cetuximab in vitro and in vivo, upregulates connexin 43 expression and phosphorylation, increases gap junction function, and inhibits the activation of Akt and NFκB in parental or cetuximab-treated parental HCT116 and CT26 cells. Resveratrol did not exhibit these effects on connexin 43-shRNA transfected cells, so connexin 43 upregulation may contribute to Akt inhibition in these cells. Given these data, resveratrol may sensitize colorectal cancer cells to cetuximab via upregulating connexin 43 to inhibit the Akt pathway.